Regional determinants of attitudes towards immigrants - Julia Peter; Silke Übelmesser (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
Attitudes toward immigrants play a crucial role in voting behaviour and political decision-making. Such attitudes are shaped by individual characteristics, but the regional environment may also be important. This paper examines how individual attitudes toward immigrants are related to the economic, political, and social environment. We use individual-level data based on a large-scale representative survey and district-level administrative data. Specifically, we examine regional variation in economic growth, voting patterns, and characteristics of the immigrant population and their relation to beliefs about and attitudes toward immigrants. We also use an information experiment in which information about the actual characteristics of the immigrant population in Germany is provided and assess its impact on attitudes toward immigrants in the regional context. Our results suggest that the impact of the environment - over and above individual characteristics - is small and depends on the type of attitude.
Keywords: C90; D83; F22; J15; R11; R23; 330; attitudes; immigrants; regional determinants; economic concerns; policy preferences